Educação em saúde para prevenção de quedas em idosos residentes em instituições de longa permanência na cidade de João Pessoa/PB - Dantas, Eveline Emilia de Barros (2024)
Introduction: Health education aimed at the elderly can play a fundamental role in preventing health problems and promoting healthier lifestyles. Accidental falls in residents of long-term care institutions for the elderly (LTCF) are a public health problem, due to the context of social and health fragility, increased risk of falls and their consequences. Objective: The general objective of this dissertation was to evaluate the existence and types of health education actions focused on preventing falls for elderly residents in two philanthropic ILPIs in the city of João Pessoa-PB, Lar da Providência Carneiro da Cunha and House of Divine Mercy. Methods: In the first phase of the research, of a bibliographic nature, a narrative review of the literature was carried out, which resulted in the publication of a digital book chapter, while in the second phase, an observational study was carried out in the aforementioned ILPI, which enabled the elaboration of a original article. In the field research, structured interviews were carried out with 31 residents, regardless of the existence of a history of falls, using a form prepared by the author, in addition to reviewing the medical records of 24 elderly people who suffered falls in the last year. Results: The importance of health education aimed at preventing falls and aimed at elderly residents was addressed, as well as continuing education and training of LTCF professionals to implement preventive measures at the local level, where effective strategies include periodic assessment of the risk of falls, adapting the environment to make it safer and promoting physical activity. In the empirical research carried out in the ILPI, the sample interviewed was predominantly female, between 80 and 89 years old, functionally independent according to self-assessment; 87% responded that they walked without assistance, with the help of devices or third parties, while 30% responded that they had suffered falls in the previous year. It was observed that 41.9% reported participating in educational activities on falls prevention at the ILPI, especially lectures; 70% considered educational activities to prevent falls to be important, while 40% stated that they were instructed on such measures, but the majority were unable to answer questions about risk factors and relevant guidelines. Conclusions: There was an identification of the occurrence of educational and inconsistent actions in the ILPI, with insufficient retention of guidelines due to the low level of knowledge of residents about risk and prevention of falls. There was interest from the majority in educational activities to prevent falls, which may indicate their engagement in a future education plan to increase their functional literacy with regard to preventable accidents in LTCFs. The results of the review and field study highlight the importance of health education focused on elderly people on fall prevention in LTCFs, with the need for more frequent and consistent educational actions to strengthen knowledge and the adoption of preventive measures, employing active and appropriate methodologies for their life cycle and institutional context. This Master's Completion Work is the result of the Postgraduate Program strictu sensu Professional Master's in Family Health (PROFSAÚDE).